Developing English Material For Sharia Economy Study Program at IAIN Palopo (Language Circle: Journal of Language and Literature, 2023)
The purpose of this developmental research is to develop English material for Sharia Economy Study Program. It aims to determine the textbooks' feasibility, and to ascertain students' responses to the ESP textbooks. The ADDIE Research and Development (RD) model is used in this study. The feasibility study of the ESP textbook reveals the following points: 1)The result of  validation from the material  expert validation was 94,11 % qualified as “Very good”,the language expert was 80% qualified as “Good.”, and  the layout expert was  92,4%  qualified as “Very Good.”. In addition, the students’ perception results got a mean score of 4,28 with 86% of the percentage, which qualified as “ Very Good”. The final product consists 10 chapter with 10 exercises of each chapter.  The developed textbook has a lot of strengths because it was created using a combination of syllabus design principles. a single unit presentation includes all four essential English skills: listening, speaking, reading, and writing, as well as grammar practice and vocabulary building. It indicates that the English material is capable and ready to use for Sharia Economic Study Program at IAIN Palopo.